Mucilage extraction in seeds of G. americana L. with a view to physiological potential - Dias Bezerra, Amanda Kelly; Silva, Givanildo Zildo da [UNESP]; Nascimento, Luciana Cordeiro do; Alcantara Bruno, Riselane de Lucena; Ferrira Medeiro, Jose George (Univ Federal Ceara, Dept Geol, 2015)
Belonging to the Rubiaceae family, the fruit-bearing plant, genipapo (G. americana L.), is widely distributed in humid tropical and subtropical regions of Latin America. The seeds present a thick adherent mucilage which can be harmful to germination, favouring the development of microorganisms; action is therefore needed for its removal. Given the above, the aim of this study was to evaluate the physiological potential of batches of genipapo seeds under different methods of extraction of this mucilage. Fruits of four genipapo mother plants from the town of Areia in the state of Paraiba, Brazil, were submitted to the following methods for the extraction of mucilage from the seeds: manual by sieve, running water and sand; fermentation; centrifugation and H2SO4. The physiological potential of the seeds was evaluated for water content, germination, first count and germination speed index, length and dry weight, seedling emergence and health test. The experimental design was completely randomised with mean values being compared by Tukey test (p<0.05). Seed moisture content was similar between batches. The different methods for extracting the mucilage from the genipapo seeds under evaluation did not affect germination, maintaining viability; when evaluated for vigour however, the seeds extracted by sieve were seen to be superior compared to the other methods. The method for the removal of mucilage from genipapo seeds using a sieve and sand gave seeds with high physiological potential, having no influence on the quality of health of those seeds.
Keywords: Genipapo; Mucilage plant; Beneficiation